2020
DOI: 10.1177/0003065120939298
|View full text |Cite
|
Sign up to set email alerts
|

Stretching the Analytic Frame: Analytic Therapists’ Experiences with Remote Therapy During COVID-19

Abstract: Remote therapy has been used by analytic therapists for quite some time, though many have been reluctant to use it regularly, out of concern that it might distort analytic frame and relational dynamics. Now the Covid-19 pandemic has forced therapists to make a sudden, across-the-board transition to remote therapy. This study reports on survey responses from 190 analytic therapists on their transition to online therapy via videoconferencing during the pandemic and their previous experience with remote therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 13 publications
9
85
1
2
Order By: Relevance
“…Lockdown and shelter-in-place measures have been employed to help alleviate the burden on healthcare systems worldwide. These measures have come at a high cost, resulting in job reductions, educational disruptions, and social restrictions [ 1 ] The reorganization of medical departments and health professional resources in order to prioritize care for COVID-19 patients has led to the strong reduction of quality of care and prevention of chronic diseases [ 2 , 3 , 4 ]. Moreover, the increased pressures on healthcare workers—including increased risk of infection and vicarious trauma among frontline healthcare workers—suggests the importance of monitoring and responding to the distress experienced by those on the frontlines of the ongoing pandemic [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lockdown and shelter-in-place measures have been employed to help alleviate the burden on healthcare systems worldwide. These measures have come at a high cost, resulting in job reductions, educational disruptions, and social restrictions [ 1 ] The reorganization of medical departments and health professional resources in order to prioritize care for COVID-19 patients has led to the strong reduction of quality of care and prevention of chronic diseases [ 2 , 3 , 4 ]. Moreover, the increased pressures on healthcare workers—including increased risk of infection and vicarious trauma among frontline healthcare workers—suggests the importance of monitoring and responding to the distress experienced by those on the frontlines of the ongoing pandemic [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nos estudos analisados sobre psicoterapia online, a videoconferência foi a Tecnologia de Informação e Comunicação mais utilizada 4,5,6,7,8 . Pode-se pensar que a preferência por chamadas de vídeos se deve ao fato de que possibilita, de certo modo, a reprodução de um setting terapêutico o mais parecido possível com o presencial.…”
Section: Resultsunclassified
“…Estudos mostraram que os profissionais mais velhos e com mais experiência clínica apresentaram maior atitude positiva frente aos atendimentos online, visto que conseguiam manter a técnica psicoterapêutica e a garantia da eficácia do tratamento, apesar dos desafios no uso das tecnologias. Já para os psicoterapeutas mais jovens, os desafios estiveram atrelados ao manejo clínico na psicoterapia online, o que colocava sentimentos de ansiedade e insegurança frente a eficácia da modalidade de atendimento online oferecida 7,8 . Estudos prévios realizados já indicavam a eficácia do atendimento online, pontuando também as ressalvas que os terapeutas tinham com o uso dessa modalidade e a maior aceitação por parte dos pacientes 2,3 .…”
Section: Resultsunclassified
“…If this is so, the impact of the pandemic on the acceptance of remote training methods may be profound, even in the absence of empirical data on teleanalysis. As Békés and colleagues have shown (2020), after fewer than two months of experience conducting teletherapy and teleanalysis during the pandemic, clinicians already viewed the modalities more positively. Our appreciation of the strengths and weaknesses of teleanalysis and its impact on training is sure to grow in the ensuing months.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 190 psychoanalytically oriented therapists gathered through professional networks and conducted shortly after the first U.S. stay-at-home orders (Békés et al 2020), found that only a minority of respondents experienced any of the challenges theorists had predicted for teletherapy and teleanalysis, such as difficulty keeping professional boundaries (23.2%), less authenticity (22.1%), difficulty reading the patient’s emotions (27.4%), or feeling less connected to the patient (29.5%). Instead, most respondents felt as confident and competent working remotely as when conducting an in-person treatment and, accordingly, reported a reduction in their previously held negative attitudes toward online therapy.…”
Section: Covid-19 and The Emergency Adaptation Of Treatment And Trainingmentioning
confidence: 99%